EFFECT OF INTEGRATED WEED MANAGEMENT PRACTICES AND BIOFERTILIZERS ON WEED CONTROL EFFICIENCY AND WEED INDEX IN SOYBEAN - S. A. HUSSAIN, CH. BHARAT BHUSHAN RAO and (The Journal of Research, PJTSAU, 2019)
A field experiment was conducted to study the weed control efficiency varied with the weed management practices. The pre-emergence application of pendimethalin @1.0 kg a.i ha-1 reduced the weeds by 50-60 per cent and thus largely eased out the crop-weed competition during early seedling establishment stage. The weed control efficiency was 80 per cent at 40 days due to integrated weed management and hand weeding at 25 days. This is the crucial time when the crop should be free of weeds. Maximum weed control efficiency of 96-97 per cent was at 60 days due to hand weeding at 25 and 45 DAS. This was much higher than the weed control efficiency of 68-69 per cent due to integrated weed management at this stage. The weed control efficiency was 72-73 per cent at 40 days and 62-64 per cent at 60 days due to pre and post emergence application of herbicides. Low weed index of 4.64 during 2014 and 5.30 during 2015 was due to the integrated weed management treatment. Thus this treatment can be an option to the farmer by losing 4-5 per cent expected seed yield of soybean if labour is not available or manual weeding is not possible after rains. The pre and post emergence application of weedicides recorded weed index of about 18 during the 2 years. But, the weed index in un-weeded crop was 52-53 per cent. If the farmers are confronted with the problem of weeding mainly due to severe labour shortage as often encountered, it is better to forego 18 per cent yield reduction by adopting the pre and post emergence herbicide applications than to lose half the production by leaving the crop to grow freely with the weeds.